PENGARUH PEMBERIAN KOMPOS LIMBAH ORGANIK TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS (Zea mays sacharata Sturt) PADA TANAH INCEPTISOL - Rika Husna; Muyassir Muyassir; Syamaun Ali (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2017)
Organic mater is one of the important component in the soil, can improve the soil feature of physical chemistry especially in marginal soil with the result, it can give a better support capacity for the growth and development of plants. This research using the Factorial Randomaized Block Design 2x4 factorial model by 3 replication. This action consists of organic material factors of straw and sago palm ground, organic factor dose is 0, 10, 20 and 30 ton ha-1. The result of this result shows that there is a fact interaction between the sort of organic material and the dose through the high plan in is days after it is grown and have 1000 weight of dry shelled seed. The hight plant in is days after the highest grown and have the combination of organic material sort from sago palm ground by giving 30 ton ha-1. while for the 1000 weight of dry shelled seed is gotten in the combination of straw by giving 30 ton ha-1 dose.